The association of physical activity and carotid intima-media-thickness in adolescents—data of the prospective early vascular ageing-tyrol cohort study - Winder, Bernhard; Zollner-Kiechl, Sophia; Bernar, Benoît; Gande, Nina; Staudt, Anna; Stock, Anna K.; Hochmayr, Christoph; Geiger, Ralf; Griesmacher, Andrea; Kiechl, Stefan; Kiechl-Kohlendorfer, Ursula; Knoflach, Michael; et al. (Frontiers in Pediatrics, 2025)
BackgroundPhysical activity (PA) protects against cardiovascular disease. However, previous research has shown that high PA is associated with an increased carotid intima-media-thickness (cIMT), an independent predictor for future cardiovascular disease. Our aim was to further investigate this unexpected association with two different measurement methods of PA and two established markers for Early Vascular Ageing: cIMT and carotid-femoral pulse-wave velocity (cfPWV).MethodsThe community-based Early Vascular Ageing-Tyrol cohort study included adolescents in western Austria and northern Italy. Medical examinations included anthropometric measurements, fasting blood analysis, a physician guided interview to assess lifestyle factors, measurement of cIMT and cfPWV. PA was rated by an in-person interview on the basis of average minutes of moderate- or vigorous sports per day and by the Baecke questionnaire expressed as Baecke score (BS).ResultsComplete data set was available for 1,001 adolescents with a mean age of 17.8 years (standard deviation ±0.9 years). 558 (55.7%) of participants were female. cIMT was positively associated with both measures of PA in univariate (minutes sports per day: p < 0.001; BS: p < 0.001) as well as multivariable analysis adjusting for established cardiovascular risk factors (minutes sports per day: p = 0.001; BS: p = 0.002). Using cfPWV in a multivariate model an inverse correlation with the BS (p = 0.023) was observed, but not for minutes sports per day (p = 0.554).ConclusionIn our large community-based cohort of adolescents, PA was associated with an increased cIMT but shows a trend towards lower aortic stiffness measured by cfPWV. We hypothesize that the association of PA with increased cIMT is not caused by early atherosclerotic vessel wall changes but is rather a physiologic adaptive process of the vessel wall. Trial Registration NumberThe EVA-Tyrol Study has been registered at clinicaltrials.gov under NCT03929692 since April 29, 2019.